Etnomatematika sebagai Pendekatan Kontekstual dalam Pengembangan Literasi Numerasi: Sebuah Sintesis Konseptual - Muhammad Irfan Habibi (LPPM UNU CIREBON, 2026)
Ethnomathematics has emerged as an approach in mathematics learning that aims to create more contextual and meaningful learning experiences. This approach positions culture as an integral part of the learning process, allowing mathematical concepts to be understood through real-life activities and experiences closely related to students’ daily lives. On the other hand, strengthening numeracy literacy has become one of the major concerns in mathematics education because numeracy skills are not limited to computational abilities but also involve the ability to understand, apply, and interpret mathematical concepts in various real-life situations. This article aims to analyze the relationship between ethnomathematics and the development of numeracy literacy through a conceptual synthesis based on studies and research articles published between 2022 and 2025. This study employed a literature review approach using descriptive qualitative analysis. The data were collected from national and international scientific articles discussing ethnomathematics, contextual learning, and numeracy literacy in mathematics education. The selected articles were analyzed, compared, and synthesized to identify the development of ethnomathematics studies and their contribution to the enhancement of numeracy literacy. The findings indicate that ethnomathematics has a significant relationship with the development of numeracy literacy in mathematics learning. The integration of local culture into mathematics instruction helps students understand mathematical concepts more concretely, improves problem-solving abilities, strengthens mathematical reasoning, and encourages students to apply mathematics in contextual situations. In addition, ethnomathematics-based learning can increase students’ engagement and learning motivation because the learning materials are closely related to their cultural experiences. Based on the literature synthesis, ethnomathematics can be understood as a contextual approach that is relevant for supporting the development of numeracy literacy in mathematics learning.